Avizandum Statutes on Scots Public Law - Singh Ghaleigh, Navraj (Avizandum Statutes Ser., 2020)
This volume contains a wide-ranging selection of materials on constitutional and administrative law, human rights and civil liberties, making it essential for public law students on the Scottish LLB Law degree. This edition includes the Early Parliamentary Elections Act 2019, the Contingencies Fund Act 2020 and the Coronavirus (Scotland) Act 2020.